Anti-Trafficking and the Harm of Funding - Findlay, Joshua (Anti-Trafficking Review, 2024)
This article argues that the UK government’s anti-trafficking funding is mostly harmful, because anti-trafficking emulates and extends other arms of the immigration system—a system financed to engage in practices of impoverishment. After explaining the slow violence at work in the asylum system, I show that UK anti-trafficking work expands the reach and extends the length of that impoverishment. I finish by making two recommendations: defunding government anti-trafficking work and organising through community building.